2020
DOI: 10.1007/s10554-020-01844-2
|View full text |Cite
|
Sign up to set email alerts
|

Grading of aortic regurgitation by cardiovascular magnetic resonance and pulsed Doppler of the left subclavian artery: harmonizing grading scales between imaging modalities

Abstract: Transthoracic echocardiography (TTE) and cardiac magnetic resonance (CMR) are current standard for assessing aortic regurgitation (AR). Regurgitant fraction (RF) can also be estimated by Doppler examination of the left subclavian artery (LSA-Doppler). However, a comparison of AR grading scales using these methods and a TTE multiparametric approach as reference is lacking. We evaluated the severity of AR in 73 patients (58 ± 15 years; 57 men), with a wide spectrum of AR of the native valve. Using a recommended … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…AR grading in 2DPC and TTE – After assignment of 2DPC measurements into AR severity according to the classification of Spampinato et al [ 9 ], 2DPC measurements revealed the same AR grading as TTE in all patients with one exception ( κ = 0.88). One patient with a bicuspid aortic valve and eccentric regurgitant jet was classified as moderate AR in TTE, whereas 2DPC measurements showed a regurgitant fraction of 45%.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…AR grading in 2DPC and TTE – After assignment of 2DPC measurements into AR severity according to the classification of Spampinato et al [ 9 ], 2DPC measurements revealed the same AR grading as TTE in all patients with one exception ( κ = 0.88). One patient with a bicuspid aortic valve and eccentric regurgitant jet was classified as moderate AR in TTE, whereas 2DPC measurements showed a regurgitant fraction of 45%.…”
Section: Resultsmentioning
confidence: 99%
“…For intra-reader agreement, one reader repeated all measurements after 10 weeks. For correlation with TTE, 2DPC measurements of every patient were assigned into AR severity grades according to Spampinato et al [ 9 ].
Fig.
…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CMR phase contrast is accurate and reproducible in AR assessment with the estimation of the regurgitant volume and regurgitant fraction. We labelled a regurgitant fraction of more than 30% as severe [46]. Although in some studies it has been suggested that AS progresses faster in BAV than in the tricuspid aortic valve [39], a recent large study by Michelena et al [40] showed that BAV and tricuspid aortic valve stenosis have similar progression rates, with evidence of accelerated progression (non-linearity) in those attaining severe AS.…”
Section: Aortic Regurgitationmentioning
confidence: 99%
“…The CMR phase contrast is accurate and reproducible in AR assessment with the estimation of the regurgitant volume and regurgitant fraction. We labelled a regurgitant fraction of more than 30% as severe [46].…”
Section: Aortic Regurgitationmentioning
confidence: 99%